Analysis Of Physical And Mental Workload Using Nasa-Tlx And Cvl Methods In Umkm Berkah Toys - Muhammad Kelvin Alfindo; Boy Isma Putra (Universitas Muhammadiyah Sidoarjo, 2022)
Berkah Toys is one of the UMKM engaged in the production of surpets, dolls. mattresses and pillows that utilize HDP (High Density Padding) and dakron (Silicon) as the main raw materials. When sales are rising, UMKM owners will apply an excessive overtime policy, resulting in a decrease in the worker attendance rate by 20%, which is as many as 2-3 workers out of a total of 13 workers. In addition to resulting in decrease in attendance, excessive overtime also causes fatigue in workers, both physical fatigue and mental fatigue. Therefore, workload strengthening must be carried out on UMKM workers of Berkah Toys, the methods used are the NASA-TLX (National Aeronautics and Space Task Load Index) and CVL (Cardiovascular Load) methods. From the results of research conducted for the NASA-TLX methods, the factors that most affect workload are performance (22,32%) and physical needs (21,64%) while from the CVL method it is known that there are 38 % of workers who experience physical fatigue, namly as many as 5 production workers.